The VENERE Study: EffectiVenEss of a Rehabilitation Treatment With Nordic Walking in ObEse or OveRweight Diabetic PatiEnts With Cardiovascular Disease - Anna Torri, MD; Eleonora Volpato, PsyD, PhD; Giampiero Merati, MD; Martina Milani, MD; Anastasia Toccafondi; Damiano Formenti, PhD; Francesca La Rosa, PhD; Simone Agostini, PhD; Cristina Agliardi, PhD; Letizia Oreni, MSc; Alice Sacco, MD; Marta Rescaldani, MD; et al. (CJC Open, 2024)
Background: Nordic walking (NW) has several potential benefits for individuals with cardiovascular (CV) disease, type 2 diabetes, and obesity and/or overweight. NW improves cardiovascular health, including exercise capacity and blood pressure control. NW enhances glycemic control and insulin sensitivity in diabetes, and aids in weight management and body composition improvement. NW offers additional advantages, such as improvement in muscular strength, joint mobility, physical activity levels, and psychological well-being. Methods: This open-label study with 3 arms will aim to evaluate the efficacy, safety, and adherence to exercise prescription in obese and/or overweight diabetic patients with CV complications. The primary objective will be to assess the CV performance of participants after a 6-month and a 12-month follow-up period, following a 3-month NW intervention, compared with standard rehabilitation, and with cardiological counseling (control group) training lasting 3 months. Results: The results of the study will provide valuable insights into the comparative effectiveness of a NW intervention vs standard rehabilitation and control group training in improving CV performance in obese and/or overweight diabetic patients with CV complications. Additionally, safety and adherence data will help inform the feasibility and sustainability of the exercise prescription over an extended period. Conclusions: These findings may have implications for the development of tailored exercise programs for this specific patient population, with the aim of optimizing CV health outcomes. Clinical Trials Registration: NCT05987410 Résumé: Contexte: La marche nordique offre plusieurs bienfaits potentiels aux personnes atteintes d’une maladie cardiovasculaire (CV), de diabète de type 2, de surpoids ou d’obésité. Elle améliore la santé cardiovasculaire, notamment l’endurance à l’effort et la régulation de la pression artérielle, en plus de favoriser l’équilibre glycémique et d'accroître la sensibilité à l’insuline chez les personnes diabétiques. Elle facilite également la gestion du poids et l’amélioration de la composition corporelle. Par ailleurs, la marche nordique présente d’autres avantages, comme l’augmentation de la force musculaire, de la mobilité articulaire, du niveau d’activité physique et du bien-être psychologique. Méthodologie: Cette étude ouverte à 3 groupes vise à évaluer l’efficacité, la sécurité et l’observance des exercices prescrits chez des sujets diabétiques obèses ou en surpoids présentant des complications CV. Le principal objectif consistera à évaluer la performance CV des participants au cours d'une période de suivi de 6 et 12 mois après un programme de marche nordique de 3 mois, comparativement à un programme de réadaptation standard et à un programme d’encadrement en soins CV (groupe témoin) de 3 mois. Résultats: Les résultats de l’étude fourniront de précieux renseignements sur l’efficacité d’un programme de marche rapide comparativement à un programme de réadaptation standard et à un programme d’encadrement (groupe témoin) pour améliorer la performance CV chez des sujets diabétiques obèses ou en surpoids présentant des complications CV. Les données relatives à la sécurité et à l’observance permettront également d’évaluer la faisabilité et la viabilité de la prescription d’exercices sur une longue période. Conclusions: Ces résultats pourraient s’avérer utiles dans l’élaboration de programmes d’exercices spécifiquement conçus pour cette population de patients, afin d’optimiser les résultats en santé CV. Numéro d’inscription de l’essai clinique: NCT05987410